PKM : Pelatihan Stimulasi Deteksi Dini Perkembangan Dalam Rangka Optimalisasi Tumbuh Kembang Anak Balita - Khofiyah, Nidatul; Fitriahadi, Enny Fitriahadi (Jurnal Pengabdian Dharma Bakti, 2019)
The success of development is closely related to the quality of good human resources. Establishment of optimal quality of human resources, both physically and psychologically is very dependent on the process of growing and developing at an early age. Monitoring the growth and development of children that is carried out appropriately and directed guarantees more optimal growth and development of children that makes children of high quality, intelligent, responsible and efficient for the nation and the nation. Based on the results of observations, the Posyandu of Beji Sidoarum has been limited to growth checks only in the implementation of posyandu related to growth, namely weighing and measuring height. Development checks have never been carried out because of the limitations of cadres and not every month the puskesmas midwives conduct health checks at the posyandu. There has never been a Posyandu health cadre who participated in the early growth growth stimulation and intervention training. Therefore, increasing education for cadres related to growth and development is needed to improve the quantity and quality of services at this posyandu. Outputs produced are 1) Compilation of booklets/modules as information media, 2) results of examination of fallen children under five, 3) Ability of cadres and mothers of children under five in stimulation and early detection of development using KPSP, 4) publication. The results obtained by cadres and mothers of children under five in carrying out stimulation and early detection using KPSP independently. Based on this, it is expected that the implementation of activities for monitoring the growth of children under five can run routinely at the posyandu.Keywords: early detection, training, stimulation, growth and development